The Effect of Clinical Preceptor Training on Student Satisfaction in Clinical Practice Guidance - Ernik Rustiana; Ernawati Tri Handayani (Science Midwifery, 2020)
Clinical/field practical learning is a learning activity held in practice places such as hospitals, clinics, health centers, and communities. Clinical Instructors are responsible for educating and supporting students during clinical practice and facilitating learning in the practical field. The research objective was to identify the effect of mentor preceptor training by clinical instructors on student satisfaction in guiding clinical practice in Midwifery Study Program, University of Tulungagung. Analytical observational research design with the cross-sectional approach. The population of all students of the D3 Midwifery Study Program at the University of Tulungagung has already implemented midwifery clinical practice. The sample was taken using a simple random sampling technique as many as 62 students. research instrument are questionnaire. Data were analyzed using the chi-square test. The results showed that 32 student (51.6%) were guided by CI who had attended preceptor mentor training by clinical instructors; most of the respondents, namely 46 students (74.2%), said they were satisfied with CI in guiding Clinical practice at the D3 Midwifery Study Program. Chi-square statistical test obtained p-value 0.000 <0.05 it’s means that there is an effect of mentor preceptor training by clinical instructors on student satisfaction in guiding clinical practice in D3 Midwifery Study Program, University of Tulungagung. Preceptor mentor training can provide satisfaction for students in guiding during clinical practice; this can happen, of course, with various factors that support its implementation, such as a standardized guidance system and preceptor ship training followed by clinical supervisors who can provide good service.